Parental Teleological Awareness Based on Research Conducted in Central Poland - Zawadzka, Edyta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2021)
The research problem discussed in this text concerns the specificity of parental teleological awareness, the components of which, in accordance with a constructed theoretical framework, are parental attitudes towards the child-rearing goals, types of their teleological awareness and the content of the child-rearing goals. The considerations are based on the results of the surveys that were conducted in central Poland. The research sample consisted of 212 parents who have filled the survey questionnaire that consisted of both open-ended and closedended questions. The results show that within the study group of parents, the child-rearing activity is usually deliberate, and that one can identify 4 types of parental teleological awareness (passive and active, as well as primary and secondary), with active and secondary being the dominant ones. Regardless of the fact that the content of the child-rearing goals within the said group is characterised by diversity, they usually form internally coherent system. In terms of preferred goals, one can observe the tendency among the parents to declare the intentions to pursue the objectives related to universal values, having a negotiable meaning, more often than not with individualistic rather than social qualities, and those assuming the child’s subjectivity in the process of achieving them. The stated (verbalized) goals usually refer to postulated vision of a human being or his/her features.